Identifikasi Rizobakteria Asal Tanaman Cabai Berdasarkan Sekuen Gen 16S rRNA - Jumsu Trisno; Yusniwati . (Jurnal Fitopatologi Indonesia, 2012)
Rhizobacteria was reported to have a potential role as inducer of systemic resistance in several host plants. Five isolates of rhizobacteria (RbTD1-3, RbTD1-8, RbPdGN-3, RbAg1-5, RbLPK1-9) were isolated from rhizosphere of chillipepper plants in West Sumatera. Identification of rhizobacteria was conducted by polymerase chain reaction using primers 27F and 1525R which amplified 16S rRNA region. DNA fragment of 1.5 kb was succesfully amplified from 4 isolates (RbLPK1-9, RbPdGN-3, RbTD1-3 and RbTD1-8) and subjected to direct sequencing. Phylogenetic analysis based-on 16S rRNA sequences showed that isolate RbLPK1-9 has a close relationship with Pseudomonas fluorescen Biotipe G (92%), whereas isolates RbTD1-3, RbTD1-8 and RbPdGN-3 have a close relationship with Bacillus subtilis 10407 (57%).Key words: polymerase chain reaction, rhizobacteria, 16S rRNA